2006
DOI: 10.1152/ajprenal.00517.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline protects against endotoxin-induced acute renal failure in mice

Abstract: . Pentoxifylline protects against endotoxin-induced acute renal failure in mice. Am J Physiol Renal Physiol 291: F1090 -F1095, 2006; doi:10.1152/ajprenal.00517.2005.-Acute renal failure (ARF) in septic patients drastically increases the mortality to 50 -80%. Sepsis induces several proinflammatory cytokines including tumor necrosis factor-␣ (TNF-␣), a major pathogenetic factor in septic ARF. Pentoxifylline has several functions including downregulation of TNF-␣ and endothelia-dependent vascular relaxation. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 41 publications
7
47
2
1
Order By: Relevance
“…In this endotoxemic shock model of AKI, pentoxifylline, contrary to previous results in the normotensive endotoxic model of AKI, [7] did not exhibit a protective effect on GFR. However, in the normotensive endotoxic model, pentoxifylline totally blocked the rise in TNF.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this endotoxemic shock model of AKI, pentoxifylline, contrary to previous results in the normotensive endotoxic model of AKI, [7] did not exhibit a protective effect on GFR. However, in the normotensive endotoxic model, pentoxifylline totally blocked the rise in TNF.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in the normotensive endotoxic model, pentoxifylline totally blocked the rise in TNF. [7] In contrast, in the present study, pentoxifylline had no detectable effects on the dramatic rise in TNF, which occurred in the endotoxemic shock model of AKI. Pentoxifylline is a phosphodiesterase inhibitor that increases cyclic AMP, a known vasodilator.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Lowes and colleagues, Wei and associates in 2011, Rishi et al, all documented raised serum ALT and AST levels with hepatic architectural distortion in response to LPS administration. 15,19,20 Despite questionable role, research outcomes however exhibits beneficial results of corticosteroids in sepsis induced hepatotoxicity. Dexa- methasone was administered at a physiologically applicable dose of 3mg/kg (21) (2013) demonstrated that dexamethasone (given 1 hour before LPS) abolished LPS produced liver injury as proved by restoration of serum ALT and hepatic inflammation.…”
Section: Discussionmentioning
confidence: 99%